Insulin-induced reactivation of an inactive herpes simplex thymidine kinase gene. - Clough, D W (1984)
A line of mouse cells transformed with ultraviolet-irradiated herpes simplex virus type 1 and containing a methylated and inactive viral thymidine kinase (TK) gene was treated with insulin in an attempt to induce expression of the inactive gene. Insulin was found to be capable of inducing the inactive TK gene in these cells. The induction of the TK+ phenotype was dose dependent (from 1-100 micrograms of insulin per ml), and the TK activity induced was shown to be of viral origin. Analysis of the methylation pattern of the viral TK gene by using the methylation-sensitive restriction endonucleases Sma I, Hpa II, and Hha I revealed that the active viral TK gene in the parental transformed cells was hypomethylated, whereas the inactive TK gene in the uninduced TK- cells was methylated. The active TK gene in three insulin-induced TK+ lines also was methylated, but the methylation patterns in the insulin-induced lines all were different from the uninduced TK- line. These data suggest that extensive hypomethylation of the inactive TK gene is not required for insulin induction. Four other transformed lines containing an inactive viral TK gene were tested for insulin inducibility, but insulin was unable to induce expression of the TK gene in any of the other lines. Thus, insulin inducibility does not seem to be a function of the viral TK gene itself. These results suggest that insulin inducibility of the viral TK gene may be a reflection of the region of the host genome into which the TK gene was integrated.